2017
DOI: 10.1002/pc.24506
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance starch/clay bionanocomposite for textile warp sizing

Abstract: In this study, an oxidized starch (OS)/montmorillonite (MMT) nanocomposite was prepared via a solution intercalation method. Before incorporating MMT into OS, MMT was organically modified with 20 wt% of octadecyl dimethyl tertiary amine followed by a hydrophilic ball‐milling treatment in the presence of urea, ethanol, and formaldehyde (two‐step processing technique). X‐ray diffraction revealed that the interlayer spacing of the MMT expanded from 1.29 to 2.00 nm after the organic modification and MMT turned int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…One of the major drawbacks of starch‐based materials can be attributed to their sensitivity to moisture and water, thus affecting its tensile properties and stability . The effect of CNF and MMT with different contents on Mu of the starch based nanocomposite films were evaluated under 68% RH at a room temperature of 20 ± 2 °C for 10 days and the results are shown in Figure and Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major drawbacks of starch‐based materials can be attributed to their sensitivity to moisture and water, thus affecting its tensile properties and stability . The effect of CNF and MMT with different contents on Mu of the starch based nanocomposite films were evaluated under 68% RH at a room temperature of 20 ± 2 °C for 10 days and the results are shown in Figure and Table .…”
Section: Resultsmentioning
confidence: 99%
“…One of the major drawbacks of starch-based materials can be attributed to their sensitivity to moisture and water, thus affecting its tensile properties and stability. [33,34] The effect of CNFand MMT with different contents on Mu of the starch based nanocomposite films were evaluated under 68% RH at a room temperature of 20 AE 2 C for 10 days and the results are shown in Figure 6 and Table 2. It is observed that the equilibrium Mu of CS film in this condition was 19.28%, which is higher than that of CS/CNFs (17.12%, 16.73%, 17.82%, 17.69%) and CS/MMTs (17.75%, 17.74%, 17.08%, 17.79%) nanocomposite films.…”
Section: Moisture Uptake Of the Filmsmentioning
confidence: 99%
“…A complete exfoliation is a difficult task, and researchers have developed several strategies to achieve it or at least to improve the dispersion degree. These strategies include Processing techniques [1,[73][74][75][76] and chemical Modification of Nanoclays and/or matrices [67,71,72,[77][78][79]. Several works can be found in the literature dealing with Thermoplastic starch/ clay Nanocomposites mainly for Packaging [78,[80][81][82][83] and agricultural applications [77,84,85].…”
Section: Nanocomposites Based On Thermoplastic Starch and Nanoclaysmentioning
confidence: 99%
“…Starch-based films are brittle and hydrophilic, therefore limiting their processing and application. [16] For improving the properties, [17][18][19] of the starch polymer, [20] starch can be mixed with various synthetics, [21,22] and natural polymers [23] such as multilayer structures, [24,25] with aliphatic polyesters, chitosan, blends with natural rubber and composites with fibers. [26,27] The modified properties of biopolymer [28][29][30][31][32] can be utilized in different applications such as polymer electrolytes for lithium batteries, [33] electronic applications, [34,35] as a membranes for separation, as a catalysis, lab-on-chip technologies, stimuli-responsive shape memory polymer, [36] biomedical application, [37,38] orthopedic surgery, [39] tissue engineering, and 3D printed scaffolds for bone tissue regeneration.…”
Section: Doi: 101002/star202000108mentioning
confidence: 99%